EARLY DETECTION OF INHERITED RETINAL DISEASES IN INFANTS USING MACHINE LEARNING - CH. Venkateswarlu,Pathan Fareedh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Inherited retinal diseases lead to multiple visual impairments in children, often resulting in early-onset blindness. The healthcare sector recognizes machine learning as a crucial and widely employed concept globally. Its significance lies in its ability to aid doctors in expediting the diagnostic process. By harnessing the power of machine learning, healthcare professionals can enhance their diagnostic accuracy and provide timely and effective interventions for children affected by these debilitating conditions.